2013
DOI: 10.1007/s13337-013-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of Highly Pathogenic Avian Influenza H5N1 Virus in Poultry Faeces at Different Temperatures

Abstract: Highly pathogenic avian Influenza (HPAI) is an important zoonotic disease and is becoming a great threat to poultry industry. India has experienced continual outbreaks of H5N1 HPAI virus since February, 2006 especially in Eastern India. Survivability in poultry faeces is an important determinant in evaluating the persistence of the virus in the poultry sheds and their vicinity. In this paper, survivability of Indian H5N1 HPAI virus in dry and wet poultry faeces at 42, 37, 24 and 4°C, respectively is reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Thus, the HPAI epidemic seemed to be waning in Germany since April 2017 (Figure 4). Rise in ambient temperature and increasing UV radiation as well as lower densities of overwintering waterfowl on lakes and rivers may have influenced the decrease of observed cases since the tenacity of AIV is in general regarded as low (13, 14). However, in August 2017 feral mute swans in central Germany were found dead and tested positive for HPAIV H5N8.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the HPAI epidemic seemed to be waning in Germany since April 2017 (Figure 4). Rise in ambient temperature and increasing UV radiation as well as lower densities of overwintering waterfowl on lakes and rivers may have influenced the decrease of observed cases since the tenacity of AIV is in general regarded as low (13, 14). However, in August 2017 feral mute swans in central Germany were found dead and tested positive for HPAIV H5N8.…”
Section: Resultsmentioning
confidence: 99%
“…The higher frequencies occurred in the cooler months ( Figure 4A, Table 1, Appendix 1) perhaps due to the higher demand for poultry breeding flocks to produce meat and eggs to meet the needs during the school season, the harvest season of green feed and during Christmas. It has also been reported that the virus survival time in the cold environment is enhanced (Paek et al, 2010;Kurmi et al, 2013). Previous reports claim that subtype H5N1 infections in poultry are associated with poultry densities and has been highly correlated with crop production (Bodbyl-Roels et al, 2011;Fuller et al, 2013;El-Masry et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Avian influenza virus, for example, was detectable in wet and dry chicken faeces stored at 4°C for up to 8 weeks and for 5 days at 24°C (Kurmi et al . ). Swine fever virus has been shown to survive in faeces collected from experimentally infected pigs for approx.…”
Section: Discussionmentioning
confidence: 97%
“…While information on the survival of bacteriophages is limited, extensive survival studies have been undertaken with other viruses (Nazir et al 2011). Avian influenza virus, for example, was detectable in wet and dry chicken faeces stored at 4°C for up to 8 weeks and for 5 days at 24°C (Kurmi et al 2013). Swine fever virus has been shown to survive in faeces collected from experimentally infected pigs for approx.…”
Section: Discussionmentioning
confidence: 99%